Quantitative redox biology of exercise - Nikolaidis, M. G.; Margaritelis, N. V.; Matsakas, A. (International Journal of Sports Medicine, 2020)
Biology is rich in claims that reactive oxygen and nitrogen species are involved in every biological process and disease. However, many quantitative aspects of redox biology remain elusive. The important quantitative parameters you need to address the feasibility of redox reactions in vivo are: rate of formation and consumption of a reactive oxygen and nitrogen species, half-life, diffusibility and membrane permeability. In the first part, we explain the basic chemical kinetics concepts and algebraic equations required to perform "street fighting" quantitative analysis. In the second part, we provide key numbers to help thinking about sizes, concentrations, rates and other important quantities that describe the major oxidants (superoxide, hydrogen peroxide, nitric oxide) and antioxidants (vitamin C, vitamin E, glutathione). In the third part, we present the quantitative effect of exercise on superoxide, hydrogen peroxide and nitric oxide concentration in mitochondria and whole muscle and calculate how much hydrogen peroxide concentration needs to increase to transduce signalling. By taking into consideration the quantitative aspects of redox biology we can: i) refine the broad understanding of this research area, ii) design better future studies and facilitate comparisons among studies, and iii) define more efficiently the "borders" between cellular signaling and stress.